Cyclic Loading Test for the Small-Strain Shear Modulus of Saturated Soft Clay and Its Failure Mechanism - Zhende Zhu; Cong Zhang; Jun Wang; Peng Zhang; Duan Zhu (Geofluids)
Small-strain shear modulus, Gmax, is a key evaluation index to study the dynamic characteristics of soil in geotechnical engineering. It is widely adopted to evaluate the stiffness of soft soil in soil dynamic engineering. In this paper, the cyclic triaxial tests and resonance column tests were carried out to explore the variation of Gmax of soft clay with respect to various confining stresses, cyclic shear stress ratios, pore pressures, and effective stress paths. Test results indicated that the effective stress decreased gradually with the increase of the cycle shear stress ratio. The failure points were mainly concentrated in a rectangular area, defined by the normalized effective stress from 0.56 to 0.64 and the normalized shear modulus from 0.72 to 0.78. Additionally, a short pause caused a small increase of 1-2% in Gmax as well as pore pressure. This study demonstrates that Gmax can be effectively used to characterize the failure of saturated soft clay in a more intuitive and convenient way, compared to the commonly used strain failure standards.